PENGARUH VARIASI PENGELASAN SMAW TERHADAP KARAKTERISTIK MEKANIK PADA BAJA GALVANIS - Samodro, Tegar; Salahudin, Xander; Sulistyo, Raka Mahendra (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Industrial growth, especially iron and steel, is growing rapidly today. In this industry, welding is an important aspect that needs to be considered to achieve results that meet standards. The SMAW welding process is often used to improve joint quality. This study aims to explore the effect of the combination of current strength and electrode diameter on the hardness and tensile strength of galvanized steel welded with an E6013 electrode. The results showed that the combination of current strength of 80 A and electrode diameter of 2.6 mm produced the highest hardness value of 221.5 VHN and the largest tensile strength of 358.16 MPa, with ferrite dominance in the microstructure.